THE PRACTICALITY OF POLITICAL PHILOSOPHY*. Issue 1 (12th February 2014) - Weinberg, Justin
Abstract Must principles of justice be practical? Some political philosophers, the "implementers, " say yes. Others, the "idealists, " say no. Despite this disagreement, the implementers and idealists agree on what "practical" means, subscribing to the "implementation-prediction" (IP) conception of practicality. They also seem to agree that principles of so-called "ideal theory" need not be (and often are not) IP-practical. The implementers take this as a reason to reject ideal theory as an approach to principles of justice, while the idealists do not. In this paper, I argue that we should reject the IP conception of practicality. The implementers make a mistake, then, by requiring principles of justice to be IP-practical. But the idealists make a mistake, too, by rejecting in general the requirement that principles of justice be practical. For there is a plausible alternative conception of practicality that political philosophers should accept: the "experimentation-learning" (EL) conception. EL-practicality makes for a more realistic and epistemically accessible standard of practicality, and thus should be welcomed by the realistically-inclined implementers. It also preserves a crucial role for ideal theory, so should be welcomed by the idealists, too.